CORONAVIRUS INFECTION AND ITS CONTROL THROUGH VARIOUS APPROACHES: A SHORT REVIEW - Shareef, Shoaib; Khalil, Sawera; Sharif, Muhammad Shahid (International Journal of Research -GRANTHAALAYAH, 2021)
Coronavirus is a common virus causing very serious issues to public health. This virus, SARS-COV-2, has disseminated worldwide respiratory illness, designated as COVID-19. This viral infection disturbs people in various ways. A lot of people infested due to this virus develop a mild illness and get relief soon without any sort of hospitalization. But mostly, it becomes highly severe later and the patient has to undergo shortening of breath as well as some other chest-related abnormalities like Middle East Respiratory Syndrome (MERS) and Acute Respiratory Syndrome. In this manuscript, we have discussed multiple areas like symptomatology, management approaches including Homoeopathic and Allopathic (drugs) treatments, plus vaccination. Lastly, we have put in the conclusion of overall literature, and most importantly implicated or suggested certain new research areas for the researchers to explore which may assist in preventing further spread of this threatening syndrome now and in the future.